2019
DOI: 10.1111/bpa.12801
|View full text |Cite
|
Sign up to set email alerts
|

IDH mutant lower grade (WHO Grades II/III) astrocytomas can be stratified for risk by CDKN2A, CDK4 and PDGFRA copy number alterations

Abstract: In the 2016, WHO classification of tumors of the central nervous system, isocitrate dehydrogenase (IDH) mutation is a main classifier for lower grade astrocytomas and IDH-mutated astrocytomas is now regarded as a single group with longer survival. However, the molecular and clinical heterogeneity among IDH mutant lower grade (WHO Grades II/III) astrocytomas have only rarely been investigated. In this study, we recruited 160 IDH mutant lower grade (WHO Grades II/III) astrocytomas, and examined PDGFRA amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 38 publications
5
75
1
Order By: Relevance
“…Tumors with mid-level deletion (10-30%) fared somewhat worse than those with low level deletion (< 10%), but this difference was not significant (p = 0.0636, log-rank test). Using the 2007/2016 WHO Classification histologic grading criteria, there was minimal to no separation of grade 2 and grade 3 tumors, as has been previously demonstrated by multiple groups [3,4,11]. Primary histologic grade 4 tumors had significantly decreased survival compared to histologic grades 2/3 (p < 0.0001, log-rank test).…”
Section: Both Cdkn2a Homozygous Deletion and Histologic Grade Are Indsupporting
confidence: 55%
See 1 more Smart Citation
“…Tumors with mid-level deletion (10-30%) fared somewhat worse than those with low level deletion (< 10%), but this difference was not significant (p = 0.0636, log-rank test). Using the 2007/2016 WHO Classification histologic grading criteria, there was minimal to no separation of grade 2 and grade 3 tumors, as has been previously demonstrated by multiple groups [3,4,11]. Primary histologic grade 4 tumors had significantly decreased survival compared to histologic grades 2/3 (p < 0.0001, log-rank test).…”
Section: Both Cdkn2a Homozygous Deletion and Histologic Grade Are Indsupporting
confidence: 55%
“…Additionally, some of the morphologic features used to grade IDHwt tumors do a poor job of stratifying IDHm astrocytoma survival, particularly mitotic activity [2][3][4]. To address these shortcomings, a number of groups have investigated molecular correlates of aggressive behavior in IDHm astrocytomas [5][6][7][8][9][10][11]. Based on these studies, homozygous deletion of the CDKN2A gene, which encodes the cell-cycle regulators p16INK4A and p14ARF, has emerged as a leading candidate molecular marker of high-grade behavior in these tumors [3,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been shown to predict the response to temozolomide (TMZ) [48], the standard-of-care chemotherapeutic agent approved for GBM [94]. A separate group of adult diffuse gliomas characterized by activating IDH1 (IDH1mut) or IDH2 (IDH-2mut) mutations comprise 1p/19q intact astrocytomas and 1p/19q co-deleted oligodendrogliomas, with varying grades (II-IV) and survival rates [89], further displaying, e.g., PDG-FRA and CDK4 amplification, CDKN2A/B deletion, ATRX, TP53, or TERT promoter mutations [60,83,116], as well as a glioma CpG Island Methylator Phenotype (G-CIMP) [33,79]. Several studies point towards an evolution of diffuse gliomas upon treatment and recurrence, where IDH1/2mut astrocytomas show most and IDHwt GBMs least changes in relapsed tumors [5,29,38,57].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the deletion did not exist in grade II astrocytoma. Although another study by Appay et al confirmed this finding [2], Yang et al identified this homozygous deletion in 12% of grade II tumors [16]. One possible reason for such a discrepancy is that while Shirahata et al [13] used pHH3 antibody, which is sensitive as mentioned above, Yang et al [16] did not; without using pHH3 antibody, they might have identified fewer mitoses, and thus regarded grade III tumors in other studies as grade II ones, resulting in a lower rate of grade III.…”
Section: Cdkn2a/b Homozygous Deletion and Other Genetic Alterationsmentioning
confidence: 91%